High-yield thermalized positronium at room temperature emitted by morphologically tuned nanochanneled silicon targets. (7th May 2021) - Mariazzi, S; Caravita, R; Zimmer, C; Rienäcker, B; Camper, A; Belov, A; Bonomi, G; Brusa, R S; Castelli, F; Consolati, G; Doser, M; Gjersdal, H; et al.
Abstract: Nanochanneled silicon targets with high positron/positronium (Ps) conversion rate and efficient Ps cooling were produced. Morphological parameters of the nanochannels, such as their diameter and length, were adjusted to get a large fraction of thermalized Ps at room temperature being emitted into vacuum. Ps cooling measurements were conducted combining single-shot positron annihilation lifetime spectroscopy and Doppler spectroscopy of the 1 3 S → 2 3 P transition. 2 γ –3 γ annihilation ratio measurements were also performed to estimate the positron/Ps conversion efficiency. In a converter with nanochannel diameter of 7–10 nm and depth of 3.89 μ m, ∼28% of implanted positrons with an energy of 3.3 keV was found to be emitted as Ps with a transverse kinetic energy of 11 ± 2 meV. The reduction of the nanochannels depth to 1.13 μ m, without changing the nanochannel diameter, was found to result in a less efficient cooling, highlighting the presence of Ps reflection from the bottom end of nanochannels.